Eureka : An essay on the material and spiritual universe - Poe,Edgar Allan (Hesperus Press, 2002)
The year is 1941. Verna Wilensky has been electrocuted in her bathtub, leaving a lower-middle-class life, no survivors, and a bank account packed with almost a hundred thousand dollars. Mysterious checks have consistently come to her for more than twenty years, most drawn from a bank in San Pietro, a town once known as Eureka." "Eureka was a town that used to be a bootlegger's paradise and a gangster's dream. Now it is the rebuilt metropolis where Sheriff Thomas Culhane is launching a bid to be the Golden State's next governor. But something just might threaten his ambitions. As Bannon digs deeper into Wilensky's demise, he unearths a decades-old secret that starts in a shootout, builds to a bloodbath, and could end up within the upper echelons of California's elite, forever changing the destiny of a state."--BOOK JACKET.